The Role of Academic Research in SEC Rulemaking: Evidence from Business Roundtable v. SEC - GEOFFROY, RACHEL; LEE, HEEMIN (Journal of Accounting Research, 2021)
ABSTRACT To shed light on the role that academic research plays in Securities and Exchange Commission (SEC) rulemaking, this paper examines the SEC's patterns of consumption of academic research from 2007 through 2017. We show how the Business Roundtable v. SEC ruling in 2011 increased consideration given to academic research during SEC rulemaking. We find that after the ruling, the SEC cites more papers in its proposed rules and, in particular, more papers that illustrate the costs of regulation. This change in academic citations results in fewer negative comment letters on proposed SEC regulations. We survey academics whose research was cited by the SEC, and the majority respond that the SEC's description of their work is completely or mostly accurate. When we survey general academics, their average rating of the SEC's accuracy is lower, although the rating improves regarding specific SEC quotes citing academic research. Although there is still room for a more substantive discussion of research, having a higher standard of cost‐benefit analysis leads to a more balanced discussion of academic research.